Diarrhea prevalence and water, sanitation, and hygiene (WASH) factors among internally displaced children under-five in Mekelle city, Northern Ethiopia - Misrak Gebremariam Abera; Adhena Ayaliew Werkneh; Reda Shamie Welde; Md Aminul Islam; Gebru Hailu Redae (Elsevier, 2024)
Background: This study aimed to assess the prevalence of diarrhea and associated factors among internally displaced children under-five at school camps of Mekelle City, Northern Ethiopia. Methods: A descriptive cross-sectional study was conducted in Mekelle City (Ethiopia) from July 2021 to August 2021. Fifteen out of twenty-five IDP centers with 415 children under the age of five were randomly selected. A face-to-face interview with a pretested and administered questionnaire was used to collect data. Bivariate and multivariate logistic regressions were used to identify the predictor variables. Results: The result of this study showed that the two-week prevalence of diarrhea among under-five children in Mekelle IDPs was 52.3 % (95 % Confidence Interval (CI): 47.5-56.9). The multivariate logistic regression model revealed that educational status (Adjusted Odds Ratio (AOR): 2.93, 95%CI: 1.637-5.269), children's faecal matter disposal practice (AOR: 0.49, 95%CI: 0.282-0.879), water storage period (5.53, 95%CI: 2.269-13.486), water treatment practice (AOR: 4.57, 95%CI: 2.435-8.609), cleaning practice of water storage material (AOR: 2.62, 95%CI: 1.550-4.431), water supply (AOR: 3.34, 95%CI: 1.007-11.113) and hand-washing practice (AOR: 2.50, 95%CI: 1.012-6.179) had a significant association with diarrhea prevalence. Conclusions: The prevalence of diarrhea among children under-five in the IDPs of Mekelle was significantly high, where educational status, disposal practice's of children faecal matter, drinking water storage period, water treatment practice, and cleaning practice of drinking water storage materials were the associated factors. Therefore, improvements on the water, sanitation and hygiene (WASH) facilities in the IDP centers are essential for intervention in reducing the burden of diarrhea.